Solar Urticaria: An Ambispective Study in a Long-term Follow-up Cohort with Emphasis on Therapeutic Predictors and Outcomes - David Pesqué; Andrea Ciudad; Evelyn Andrades; Dulce Soto; Ramon Gimeno; Ramon M. Pujol; Ana M. Giménez-Arnau (Medical Journals Sweden, 2024)
Solar urticaria is a rare photodermatosis with several unknown pathogenic, clinical and therapeutic aspects. This study analysed the clinical and therapeutic features of a long-term follow-up solar urticaria cohort, with a focus on omalizumab management and outcomes, and characterized omalizumab response with the use of the high-affinity immunoglobulin E (IgE) receptor (FcεRI) and the Urticaria Control Test. An observational, unicentric, ambispective study was conducted from 2007 to 2023. Solar urticaria was diagnosed in 41 patients with a median follow-up of 60 months. Thirteen patients were prescribed omalizumab, with a median treatment time of 48 months. A significant decrease in FcεRI baseline levels and subsequent median increase in Urticaria Control Test was evidenced after omalizumab prescription in all patients. Drug survival at 48 months was at 88.9%. Omalizumab stepping-down protocol led to sustained omalizumab discontinuation in only 1 patient. Median basal Urticaria Control Test was lower (p < 0.01) in patients who were prescribed omalizumab and in patients without remission. This study contributes to our knowledge of omalizumab outcomes in real-life clinical practice and highlights the pathogenic importance of IgE-mediated pathways in solar urticaria, where FcεRI emerges as a possible biomarker of omalizumab response.